2012
DOI: 10.3382/ps.2011-01968
|View full text |Cite
|
Sign up to set email alerts
|

The effects of growth rate on leg morphology and tibia breaking strength, mineral density, mineral content, and bone ash in broilers

Abstract: Fast-growing broilers are especially susceptible to bone abnormalities, causing major problems for broiler producers. The cortical bones of fast-growing broilers are highly porous, which may lead to leg deformities. Leg problems were investigated in 6-wk-old Arkansas randombred broilers. Body weight was measured at hatch and at 6 wk. There were 8 different settings of approximately 450 eggs each. Two subpopulations, slow-growing (SG; bottom quarter, n=511) and fast-growing (FG; top quarter, n=545), were create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
92
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 41 publications
10
92
1
1
Order By: Relevance
“…Bone mineralisation, commonly determined from tibia ash percentage, is an accepted measure for poultry and is assumed to be highly correlated with the overall structural strength of the skeleton. Bone mineralisation, however, is only one aspect in determining bone strength; the volume of bone tissue and micro-architectural organisation also influence bone strength and skeletal health (Rath et al, 2000;Shim et al, 2012). The results of this study may support these notions, and may explain why birds with a ratio of 1.14 : 1 Ca : nPP had high tibia ash yet still exhibited signs of impaired mobility.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Bone mineralisation, commonly determined from tibia ash percentage, is an accepted measure for poultry and is assumed to be highly correlated with the overall structural strength of the skeleton. Bone mineralisation, however, is only one aspect in determining bone strength; the volume of bone tissue and micro-architectural organisation also influence bone strength and skeletal health (Rath et al, 2000;Shim et al, 2012). The results of this study may support these notions, and may explain why birds with a ratio of 1.14 : 1 Ca : nPP had high tibia ash yet still exhibited signs of impaired mobility.…”
Section: Discussionsupporting
confidence: 56%
“…Bone breaking strength, bone density, mineral content and bone ash have been used as indicators of bone status and skeletal health (Shim et al, 2012). Bone mineralisation, commonly determined from tibia ash percentage, is an accepted measure for poultry and is assumed to be highly correlated with the overall structural strength of the skeleton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Withdrawal of VIT premix from 29 to 42 days of age has also been reported to affect bone parameters adversely (Moravej et al 2012a). Vitamin D, B6, C, and K are known to be essential for bone health as they are involved in the synthesis of bone matrix constituents (Weber 1999;Shim et al 2012). However, despite the importance of VIT and TRM premixes for bone strength, Skinner et al (1992) reported that withdrawal of both premixes from broiler finisher diets from 28 to 49 days had negligible effect on incidence of leg disorders.…”
Section: Tibia Bone Strengthmentioning
confidence: 99%
“…Bone mineral density (BMD, g/ cm 2 ) (Kim et al, 2006;Lian et al, 2004;Onyango et al, 2003;Rath et al, 2000;Shim et al, 2012;Watkins and Southern, 1992) and bone mineral content (BMC, g/cm) (Akpe et al, 1987;Almeida et al, 2008;Kim et al, 2006, Onyango et al, 2003 measurements have been used to evaluate the quality and the status of the porous structure of bone matrix. These two parameters are greatly influenced by mineral intake.…”
Section: Introductionmentioning
confidence: 99%